Innovative moments and narrative change in career counselling: a case study - da Silva, Claudia Sampaio Correa (2020)
This case study of an undecided university student has two aims: to assess the effect of life design career counselling on autobiographical reasoning and career variables, and to analyse the client's narrative transformation using the innovative moments coding system. Results show improvement in career development and organization of autobiographical narrative. The client's narrative evolved from basic to complex levels of elaboration. The spontaneous emergence of re-conceptualization innovative moments differs from previous studies and suggests that counselling length and tasks can facilitate re-conceptualization. Among the implications, the use of narrative change markers to fit counselling tasks to clients' level of development is discussed.